2022
DOI: 10.3390/met12030400
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Study on the Effect of Reduction Pretreatment on the Void Healing of Heavy Plate

Abstract: In addition to eliminating voids in a billet, the reduction pretreatment (RP) process can refine the austenite structure after reheating and can deform the residual voids, which affect the void healing behavior during insulation before rolling, and then can affect the final quality of the steel plate. In this study, the effect of the RP process on the evolution of voids in billets and steel plates was investigated by experimental and numerical simulation. RP and non-RP billets were reheated and rolled into 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Liu et al [ 17 ] investigated the HTRP process with different amounts of reduction and found that as the reduction amount of the HTRP sample increased, the size of recrystallized austenite grains significantly decreased, leading to an improvement in internal segregation. Furthermore, Ning et al [ 18 ] studied the improvement mechanism of the internal quality of steel plates in the HTRP process through finite element and phase‐field methods. They found that in addition to austenite refinement, increasing the curvature of the void surface can facilitate the diffusive healing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 17 ] investigated the HTRP process with different amounts of reduction and found that as the reduction amount of the HTRP sample increased, the size of recrystallized austenite grains significantly decreased, leading to an improvement in internal segregation. Furthermore, Ning et al [ 18 ] studied the improvement mechanism of the internal quality of steel plates in the HTRP process through finite element and phase‐field methods. They found that in addition to austenite refinement, increasing the curvature of the void surface can facilitate the diffusive healing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting approach is a process presented as "Hot Core Heavy Reduction Rolling", the properties of which are discussed in [16][17][18][19] based on numerical and analytical studies and experimental data. In addition to simulating void healing in heavy plates, by deploying FE and phase-field simulation [20], the hot rolling of clad plates has also received increased attention recently, as numerical and experimental work shows [21][22][23]. Despite these achievements, one aspect still needs to be reflected: the existing models focus on individual passes rather than on the assembly of whole rolling schedules.…”
Section: Introductionmentioning
confidence: 99%